Kajian Teknis dan Ekonimi Alat Gali-Muat dan Angkut pada Tambang Bijih Nikel di PT Mitra Tambang Gemilang di Kecamatan Pagimana Kabupaten Banggai Provinsi Sulawesi Tengah - Moh. Ilham Akbar; Zaenal; Elfida Moralista (UNISBA Press, 2023)
Abstract. PT Mitra Tambang Gemilang was established in 2018, a company engaged as a mining contractor working on extracting minerals, especially nickel. The mining system used is an open pit mining system using the Selective Mining method. The mining operation area is in Central Sulawesi, in Luwuk Banggai to be precise. In pit 1, PT Mitra Tambang Gemilang has a production target of 600,000 BCM/year and based on mining results, the production of the Sany PC 215 C excavator loading and digging equipment is 586,455.12 BCM/year and the production of the Shacman F2000 dump truck is 581,644.08 BCM/year. year, this research was carried out with the aim of knowing the comparison of production values, comparison of ownership costs and operating costs, comparison of Present Worth Cost (PWC) and Production Unit Cost (PUC) comparisons between old and new digging and loading equipment.The company plans to replace the mechanical equipment with technical and economic assessments. Technical studies include calculating the production value of each tool and for economic studies including ownership costs, operating costs, Present Worth Cost (PWC) and Production Unit Cost (PUC) values. After knowing these values, a comparison is made between the production value and PUC of the old and new equipment so that it can be seen whether the old or new equipment is more profitable. Based on the results of technical and economic studies, the production of new loading and digging equipment was 773,139.06 BCM/year and showed a production increase of 31.83%. The production of new conveyance equipment is 769,994.96 BCM/year with an increase of 32.37%, indicating that the production target has been achieved. Production Unit Cost decreased by 44.96% for digging equipment, from Rp. 3,144.75 / BCM to Rp. 2,169.36 / BCM, while the Production Unit Cost of transportation equipment decreased by 26.28% from IDR 1,862.27 / BCM to IDR 1,469.96 /BCM. These results indicate that the tool needs to be replaced because the production of new tools is greater and the operating costs are more economical than the old tools. Abstrak. PT Mitra Tambang Gemilang berdiri pada tahun 2018, perusahaan yang bergerak sebagai kontraktor pertambangan yang bekerja pada penggalian mineral terutama nikel. Sistem penambangan yang digunakan yaitu Sistem Tambang Terbuka dengan menggunakan Metode Selective Mining. Wilayah operasi penambangan berada di Sulawesi Tengah, tepatnya di Luwuk Banggai. Pada Pit 1 PT Mitra Tambang Gemilang memiliki target produksi sebesar 600.000 BCM/tahun dan berdasarkan hasil penambangan produksi alat gali-muat Excavator Sany PC 215 C adalah 586.455,12 BCM/tahun dan produksi alat angkut Dump Truck Shacman F2000 adalah 581.644,08 BCM/tahun, maka dilakukan penelitian ini yang bertujuan untuk mengetahui perbandingan nilai produksi, perbandingan biaya kepemilikan dan biaya operasi, perbandingan nilai Present Worth Cost (PWC) dan perbandingan Production Unit Cost (PUC) antara alat gali-muat dan alat angkut yang lama dan baru. Perusahaan merencanakan penggantian alat mekanis yang dilakukan dengan pengkajian secara teknis dan ekonomi. Kajian teknis meliputi perhitungan nilai produksi masing-masing alat dan untuk kajian ekonomi meliputi biaya kepemilikan, biaya operasi, Present Worth Cost (PWC) dan nilai Production Unit Cost (PUC). Setelah mengetahui nilai-nilai tersebut, maka dilakukan perbandingan antara produksi dan PUC alat lama dan alat baru, sehingga dapat diketahui apakah alat lama atau alat baru yang lebih menguntungkan. Berdasarkan hasil kajian teknis dan ekonomi, produksi alat gali-muat baru sebesar 773.139,06 BCM/tahun dan menunjukan kenaikan produksi sebesar 31,83%. Untuk produksi alat angkut baru sebesar 769.994.96 BCM/tahun dengan kenaikan sebesar 32,37% menunjukan target produksi tercapai. Production Unit Cost (PWC) mengalami penurunan sebesar 44,96% untuk alat gali-muat, dari sebesar Rp. 3.144,75 /BCM menjadi Rp. 2.169,36 /BCM, sementara Production Unit Cost (PWC) alat angkut mengalami penurunan sebesar 26,28% dari Rp 1.862,27 /BCM menjadi Rp 1.469,96 /BCM. Hasil tersebut menunjukan alat perlu diganti karena produksi alat baru lebih besar dan biaya operasi lebih hemat dibandingkan alat lama.